Kill two birds with one stone: The management of hazardous waste and the preparation of efficient adsorbents for Pb(II) were realized by the pyrolysis of penicillin mycelial dreg. (1st January 2023) - Cui, Zhiliang; Xu, Guoren; Ormeci, Banu; Hao, Jiayin
Abstract: The penicillin industry produces a large amount of penicillin mycelial dreg (PMD), potentially causing severe environmental problems without proper treatment and disposal. To achieve the goals of PMD management, the present work explored the potential of PMD as a novel feedstock to produce biochar with very high adsorption performance. PMD was pyrolyzed at 400–800 °C to prepare biochars (PMD-BCs), and the physical and chemical properties were characterized using various methods. The adsorption capacities of Pb 2+ on PMD-BC400, PMD-BC600, and PMD-BC800 were 37.04, 62.89, and 107.53 mg/g, respectively, at a temperature of 25 °C and pH of 5.0. The adsorption process of Pb 2+ on PMD-BCs can be well described by the Langmuir model and pseudo-second-order model. Mineral precipitation, ion exchange, functional group complexation and Pb 2+ -π interaction were involved in the adsorption of Pb 2+ on PMD-BCs. Moreover, mineral precipitation and ion exchange dominated Pb 2+ sorption on PMD-BCs (84.71–92.73%). This study indicates the transition of PMD to biochar for Pb 2+ adsorption is a promising method for PMD utilization. Graphical abstract: Image 1 Highlights: Biochars derived from penicillin mycelial dreg for Pb 2+ sorption were first studied. The maximum adsorption capacity of Pb 2+ on biochar was up to 107.53 mg/g. Mineral precipitation and ion exchange dominated the Pb 2+ removal mechanism.